THE ROLE OF THE GRAMMATICAL ASPECT IN TEACHING FOREIGN (ENGLISH / GERMAN) LANGUAGES - Markina, O.; Melnyk, S.; Novikov, O. (Видавництво НДУ ім. М. Гоголя, 2025)
In the conditions of russia’s current military aggression against Ukraine, a large number of Ukrainian citizens were forced to become refugees and found temporary shelter in the countries of the European Union, Great Britain, and the United States, which is a great challenge in modern conditions, since knowledge of foreign languages is a necessary condition for integration into a foreign language environment, a key necessity for communication, work, and study. The article pays attention to learning the grammatical aspect in English and German, because English is one of the most widely used languages of international communication. German is studied intensively by Ukrainian refugees because there are currently more than 1.2 million people living in Germany, about 85 thousand in Austria, and 69 thousand people in Switzerland. Teaching English and German grammar is necessary to achieve a high level of language proficiency, as it ensures the accuracy of statements, correct structuring of sentences, and correct use of words, thanks to which an average level of B1 and above is achieved, which opens the door to professional development and communication with native speakers. The principles of teaching the grammatical aspect of language include the formation of grammatical skills for the effective use of language as a means of communication, the development of grammatical competence through practical exercises and games, as well as the purposeful formation of knowledge about the morphology, syntax, and word formation of language. Grammar is the foundation of any language, since even with a good vocabulary, without knowledge of grammar, statements will be incorrect and can lead to misunderstandings. Knowledge of the rules of conjugation of verbs and cases allows you to build correct sentences and understand the interlocutor’s language, which is an integral part of communicative competence. In addition, when teaching foreign languages (in our case – English and German), grammatical knowledge (morphology, syntax, word formation) should be assimilated in a complex, as part of a complex language system, and integrated into other aspects of language activity, for example, in dialogues and other communicative situations and based on understanding the logic of language phenomena, and not only on memorizing rules.
Keywords: grammatical aspect; practical skills; intensive methods; accelerated foreign language teaching methods; grammatical competence; communicative competence